Explorations in Aromanian Morpho-Syntax: NPs, Prepositional Contexts and Infinitives - Leonardo Maria Savoia; Benedetta Baldi (Languages, 2024)
The main topic of this article is the relationship between morphosyntactic contexts and nominal inflections in Aromanian varieties of southern Albania. These varieties have a specialized inflection in the plural definite and feminine singular nouns, associated with genitive, dative, and prepositional contexts, where it is preceded by a Possessive Introducer. We present a detailed picture of the microvariation that characterizes the different systems. The broad syncretism that emerges suggests a rethinking of the syntactic status of inflections and the notion of Case. Our approach assumes that morphology is based on Merge within the syntactic computation and that sub-word elements are provided with interpretable content. This theoretical model will also guide us in the study of prepositions and their distribution.